2019
DOI: 10.4028/www.scientific.net/kem.797.20
|View full text |Cite
|
Sign up to set email alerts
|

Natural Deep Eutectic Solvent (NADES) as a Greener Alternative for the Extraction of Hydrophilic (Polar) and Lipophilic (Non-Polar) Phytonutrients

Abstract: Phytonutrients extracted from natural resources are receiving much attention among researchers due to their highly antioxidative characteristics which prevent several degenerative diseases including cardiovascular diseases and cancers. These nutraceutical compounds can be used in food, pharmaceutical and cosmetic products as natural antioxidants, preservatives, colourings and functional foods. Though much works have been reported on the extraction process, there are concerns on the health and safety risks pose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 48 publications
0
6
0
4
Order By: Relevance
“…Polarity is very sensitive to a change in water content due to the disruption of hydrogen bondings, inducing a change in the polarity index [14,25,33]. Thus, polarity is an essential aspect of NaDES and is highly related to their solubilizing ability.…”
Section: Physicochemical Characterization Of Nadesmentioning
confidence: 99%
“…Polarity is very sensitive to a change in water content due to the disruption of hydrogen bondings, inducing a change in the polarity index [14,25,33]. Thus, polarity is an essential aspect of NaDES and is highly related to their solubilizing ability.…”
Section: Physicochemical Characterization Of Nadesmentioning
confidence: 99%
“…Penelitian sebelumnya yang dilakukan oleh Yuniarti dkk pada tahun 2019 telah berhasil mengoptimasi metode ekstraksi senyawa bioaktif dari biji kopi hijau (Coffea canephora Pierre ex A. Froehner) menggunakan pelarut NADES yang terdiri dari campuran kolin klorida dan sorbitol dengan metode Ultrasound-Assisted Extraction (UAE). NADES merupakan pelarut yang sulit untuk diuapkan, namun salah satu keuntungan dari pelarut NADES adalah sifatnya yang yang aman untuk dikonsumsi sehingga ekstrak cair yang dihasilkan tidak memerlukan penguapan pelarut (6).…”
Section: Pendahuluanunclassified
“…Pelarut yang digunakan untuk mengekstraksi biji kopi hijau robusta dalam penelitian ini adalah NADES berbasis kolin klorida dan sorbitol dengan perbandingan molar 4:1. NADES merupakan suatu pelarut yang terdiri dari campuran hydrogen bond acceptor (HBA) dan hydrogen bond donor (HBD) dengan perbandingan molar tertentu yang mampu berinteraksi melalui ikatan hidrogen sehingga dapat membentuk campuran eutektik dengan titik lebur lebih rendah dari masing-masing komponen penyusunnya sehingga hasil akhir yang didapatkan berupa cairan jernih (6,33,34). Penambahan air pada proses pembuatan NADES bertujuan untuk mengurangi viskositas dari NADES karena pada viskositas yang tinggi dapat mengurangi efisiensi pada proses esktraksi (6).…”
Section: Hasil Dan Diskusiunclassified
“…Triaux and his coworkers [35] found that the most important factors for separation efficiency were extraction time and temperature. Along with their application in chromatography and biomass processing, some illustrative results of extraction of value-added compounds from biomass are described too [8,[36][37][38].…”
Section: Requirements For Extracting Agentsmentioning
confidence: 99%
“…The fact that the composition of two-or multicomponent DESs can be varied almost indefinitely in practice opens up the chance to prepare a DES with the required polarity suitable for the desired applications. The ability to modify polarity can be expected to be very important in the separation of lipophilic (non-polar) and hydrophilic (polar) nutrients from phytomass [37].…”
Section: Polaritymentioning
confidence: 99%